Promote Renewable Energies Efficiently and Effectively - Arbeitsgruppe „Energiesysteme der Zukunft“; Justus Haucap; Jürgen Kühling; Munib Amin; Gert Brunekreeft; Dörte Fouquet; Veronika Grimm; Jörg Gundel; Martin Kment; Wolfgang Ketter; Jochen Kreusel; Charlotte Kreuter-Kirchhof; et al. (Wirtschaftsdienst)
Abstract The year 2021 has brought new momentum to climate protection efforts in Germany. The amendment to the Climate Protection Act stipulates a 65 % reduction in greenhouse gas emissions by 2030 compared to 1990. A major contribution to this will come from a massive expansion of electricity generation from renewable energies. Following the tightening of the climate protection measures, the question arises as to whether the current electricity market design and the associated remuneration rules for electricity generation are still suitable for achieving the goals of security of supply and low prices stipulated in the Energy Industry Act, even with an electricity market dominated by renewable energies.